Intratracheal Ovalbumin Administration Induces Colitis Through the IFN-γ Pathway in Mice - Jung, Kyoung-Hwa; Shin, Dasom; Kim, Sejun; Min, Daeun; Kim, Woogyeong; Kim, Jinju; Lee, Gihyun; Bae, Hyunsu (Frontiers in Immunology, 2019)
Recent studies have reported an increased incidence of inflammatory bowel disease (IBD) in patients with pulmonary diseases. Despite clinical and epidemiological studies of the interplay between colitis and asthma, the diseases’ related underlying mechanisms remain unclear. In this study, we evaluated the development of colitis in a model of allergic airway inflammation. We revealed that intratracheal chronic ovalbumin (OVA) exposure induces colitis and allergic airway inflammation. Interestingly, induction of colitis was largely regulated by Th1, rather than Th2 responses, whereas allergic airway inflammation was primarily mediated by Th2 responses. Experiments in Tbx21 (T-bet) and Ifng (IFN-γ) deficient mice have confirmed that IFN-γ is a major mediator involved in OVA-induced colitis. These findings broaden current understanding of allergen induced colitis pathology and could play a role in the development of novel clinical treatment strategies for asthmatic patients who are at risk of developing colitis.